Pembuktian Dakwaan Oleh Penuntut Umum dan Pertimbangan Hakim Menjatuhkan Pidana Kumulatif - Annisa Nilasari (Verstek, 2019)
This research examines the issues of whether the indictment by the Public Prosecution Against Defendant the perpetrator of the criminal act of child abduction has used legal evidences according to Article 184 Code of Criminal Procedure and whether the judge’s consideration of imposing the imprisonment and the fne against the Defendant the perpetrator of the kidnapping of the child has been in accordance with Article 183 jo 193 paragraph (1) of the Code of Criminal Procedure.    This research is normative legal research that is both prescriptive and applied. Proving the indictment by the Public Prosecutor against the Defendant the perpetrator of the criminal act of child abduction has used the legal evidence accordance to Article 184 Code of Criminal Procedure that is witness testimony, letter, and description of defendant. The judge’s consideration of imprisonment and fnes against the Accused child abuser in accordance with Article 183 jo of Article 193 paragraph (1) of the Code of Criminal Procedure that The judge should not drop criminal to someone unless with at least two legitimate evidence he gained confdence that a crime actually occurred and that the Defendant are guilty of doing it. The Judge has tried the Defendant to be proven legally and convincingly guilty of committing the crime of kidnapping the child and imprisonment for 4 years 8 months and a fne of Rp 60,000,000, - provided that the unpaid penalty is substituted with imprisonment for 1 month.Keywords: proof, the indictment, public prosecutor, judge Considerations, kidnapping the child